Hajnóczy Péter A bajnok (filmvázlat) : feltárási kísérlet a műfaj és a szerkezet felől - és további etűdök az autotextualitás és a kísérletező eklektika irányából - Cserjés Katalin; Hajnóczy Péter (2017)
The paper examines one of Péter Hajnóczy's (1942-1981) writings (The Champion, cc. 1972) found in the author's legacy, labelled as a film sketch, corrected but not completed by the writer. A dialogue is initiated with further film-like texts of the ouvre, and radical eclecticism and permanent experimentation are identified as authorial methods.